2023
DOI: 10.1515/joc-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Free space optics communication system design using iterative optimization

Abstract: Free Space Optics (FSO) communication provides attractive bandwidth enhancement with unlicensed bands worldwide spectrum. However, the link capacity and availability are the major concern in the different atmospheric conditions. The reliability of the link is highly dependent on weather conditions that attenuate the signal strength. Hence, this study focuses to mitigate the weather and geographic effects using iterative optimization on FSO communication. The optimization maximizes the visibility distance while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In terms of visible distance, Eye diagram, BER, and quality factor, the suggested wireless optical communication performance has been compared to the literature under various weather situations. The simulation results revealed that the suggested effort achieved better performance [52].…”
Section: Journal Of Robotics and Control (Jrc)mentioning
confidence: 92%
“…In terms of visible distance, Eye diagram, BER, and quality factor, the suggested wireless optical communication performance has been compared to the literature under various weather situations. The simulation results revealed that the suggested effort achieved better performance [52].…”
Section: Journal Of Robotics and Control (Jrc)mentioning
confidence: 92%
“…The researcher have proposed the use of RF/VLC and FSOC network to overcome the challenges encountered in RF systems for online social services in [32]. The advantages of FSOL characteristics in atmospheric conditions have improve the iteration optimization which minimizes the BER for better performance [33]. The OptiSystem can be deployed to simulate different applications in the field of telecommunication and beyond.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The FSO atmospheric parameters are illustrated in Table 3. The whole system design parameters of free space optical system have been adjusted according to recent published papers [6,23] which are always based on recommendation ITU-T G.640.…”
Section: Practical System Design and Analysismentioning
confidence: 99%